2022
DOI: 10.1038/s41598-022-10842-4
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effects of ferric citrate in a mouse model of chronic kidney disease

Abstract: In chronic kidney disease, ferric citrate has been shown to be an effective phosphate binder and source of enteral iron; however, the effects of ferric citrate on the kidney have been less well-studied. Here, in Col4α3 knockout mice—a murine model of progressive chronic kidney disease, we evaluated the effects of five weeks of 1% ferric citrate dietary supplementation. As expected, ferric citrate lowered serum phosphate concentrations and increased serum iron levels in the Col4α3 knockout mice. Consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
(84 reference statements)
0
0
0
Order By: Relevance
“…Notably, ferric citrate also demonstrated anti-inflammatory properties, improved kidney function, reduced albuminuria, and decreased kidney inflammation and fibrosis. These results suggest potential renoprotective effects of ferric citrate (29).…”
Section: Ferric Citrate and Its Usagementioning
confidence: 56%
See 2 more Smart Citations
“…Notably, ferric citrate also demonstrated anti-inflammatory properties, improved kidney function, reduced albuminuria, and decreased kidney inflammation and fibrosis. These results suggest potential renoprotective effects of ferric citrate (29).…”
Section: Ferric Citrate and Its Usagementioning
confidence: 56%
“…Additionally, the patient experienced decreased kidney efficiency in 2019. In cases of chronic kidney disease (CKD), ferric citrate has been shown to be an effective source of enteral iron (29). A randomized, placebo-controlled trial in CKD patients demonstrated that ferric citrate significantly improved iron status (30).…”
Section: Ferric Citrate and Its Usagementioning
confidence: 99%
See 1 more Smart Citation
“…Another consideration is the potential beneficial role of iron in mitigating kidney fibrosis, as indicated by a list of clinical 118 , 119 and animal researches. 120 , 121 , 122 , 123 , 124 These studies propose that iron might exert different effects on the pathogenesis of kidney diseases when introduced in a proper way. The cell type in which iron deposits also seems important.…”
Section: Systemic and Renal Iron Homeostasismentioning
confidence: 99%